2022
DOI: 10.30699/ijp.2022.541660.2756
|View full text |Cite
|
Sign up to set email alerts
|

Scientometrics Analysis of World Scientific Research of Pathology and Forensic Medicine

Abstract: Scan to discover onlineBackground & Objective: This study examines the extent of scientific publications and patents in pathology and forensic medicine globally and the citation relationship between them from 2011 to 2020, indexed in the Scopus database. Methods:In this scientometric study, data were extracted from the SciVal citation database. Search feature and library study method and annual growth rate, relative growth rate, and linear model were used to retrieve and analyze the data. The scientometric ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Scientometrics analysis is valuable for gaining insights into research trends and impacts in forensic medicine and toxicology. It involves measuring and analyzing factors such as the number of articles, citation Sciences of Pharmacy Pujari AJ (2023) -10.58920/sciphar02020001 https://etflin.com/sciphar 2 frequency, and collaboration patterns among researchers (8). Through this process, scientometrics can provide a comprehensive understanding of the research landscape in these fields, identify emerging trends, evaluate research impact, and provide insights into the strengths and weaknesses of the field (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientometrics analysis is valuable for gaining insights into research trends and impacts in forensic medicine and toxicology. It involves measuring and analyzing factors such as the number of articles, citation Sciences of Pharmacy Pujari AJ (2023) -10.58920/sciphar02020001 https://etflin.com/sciphar 2 frequency, and collaboration patterns among researchers (8). Through this process, scientometrics can provide a comprehensive understanding of the research landscape in these fields, identify emerging trends, evaluate research impact, and provide insights into the strengths and weaknesses of the field (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The study found poor collaboration between academia and industry and highlighted North America as the busiest pathology and forensic medicine region. The study suggested that strengthening the link between academia and industry can enhance research in this field(8). Herve Menard et al (2021) examined the evolution of research trends within the INTERPOL International Forensic Science Managers Symposium reports over 18 years.…”
mentioning
confidence: 99%